Novel 1, 2, 3‐Triazole Derivatives as Potential Inhibitors against Covid‐19 Main Protease: Synthesis, Characterization, Molecular Docking and DFT Studies. Issue 14 (14th April 2021) - Aouad, Mohamed Reda; Khan, Daoud J. O.; Said, Musa A.; Al‐Kaff, Nadia S.; Rezki, Nadjet; Ali, Adeeb A.; Bouqellah, Nahla; Hagar, Mohamed
Abstract: The highly contagious nature of Covid‐19 attracted us to this challenging area of research, mainly because the disease is spreading very fast and until now, no effective method of a safe treatment or a vaccine is developed. A library of novel 1, 2, 3‐triazoles based 1, 2, 4‐triazole, 1, 3, 4‐oxadiazole and/or 1, 3, 4‐thiadiazole scaffolds were designed and successfully synthesized. Different spectroscopic tools efficiently characterized all the newly synthesized hybrid molecules. An interesting finding is that some of the newly designed compounds revealed two isomeric forms. The ratio is affected by the size of the attached group as well as the type of the heteroatom forming the side ring attached to the central 1, 2, 3‐triazole ring. The experimental spectroscopic data is in agreement with the DFT calculations at B3LYP 6‐31G (d, p) with regard to the geometrical conformation of the prepared compounds. The DFT results revealed that the stability of one isomeric form over the other in the range of 0.057–0.161 Kcal mol −1 . A docking study was performed using PyRx and AutoDockVina to investigate the activity of the prepared 1, 2, 3‐triazoles as antiviral agents. Bond affinity scores of the 1, 2, 3‐triazole derivatives were detected in the range of −6.0 to −8.8 kcal/mol showing binding to the active sites of the 6LU7 protease and hence could be anticipated to inhibit the activity of the enzyme. Verification of the docking results was performed using the M pro alignment of coronaviruses substrate‐binding pockets of COVID‐19 against the ligands. As per these results, it can be proposed that the title hybrid molecules are acceptable candidates against COVID‐19 for possible medicinal agents. Abstract : A series of novel 1, 2, 3‐triazole molecular hybrids with 1, 2, 4‐triazole, 1, 3, 4‐thiadiazole and/or 1, 3, 4‐oxadiazole tethers have been successfully synthesized as potential inhibitors against Covid‐19 Main Protease.